Identitas Dayak : komodifikasi dan politik kebudayaan - Maunati, Yekti (Yogyakarta : LKiS, 2004)
Differences in cultural and political identities of Dayak community in Kalimantan Timur.
Includes bibliographical references (p. [375]-398) and index.
Keywords: Dayak (Indonesian people) -- Social life and customs